A qualitative study of COVID-19 vaccine intentions and mistrust in Black Americans: Recommendations for vaccine dissemination and uptake - Dong, Lu; Bogart, Laura M.; Gandhi, Priya; Aboagye, James B.; Ryan, Samantha; Serwanga, Rosette; Ojikutu, Bisola O. (PLOS ONE, 2022)
Background COVID-19 vaccination rates among Black Americans have been lower than White Americans and are disproportionate to their population size and COVID-19 impact. This study examined reasons for low vaccination intentions and preferred strategies to promote COVID-19 vaccination. Methods Between November 2020 and March 2021, we conducted semi-structured interviews with 24 participants who expressed low vaccination intentions in a RAND American Life Panel survey; we also interviewed five stakeholders who represent organizations or subgroups in Black communities that have been highly affected by COVID-19. Results Many interviewees discussed the “wait-and-see” approach, citing that more time and evidence for vaccine side effects and efficacy are needed. Perceived barriers to COVID-19 vaccination included structural barriers to access (e.g., transportation, technology) and medical mistrust (e.g., towards the vaccines themselves, the government, healthcare providers and healthcare systems, and pharmaceutical companies) stemming from historical and contemporary systematic racism against Black communities. Interviewees also discussed strategies to promote COVID-19 vaccines, including acknowledging systemic racism as the root cause for mistrust, preferred messaging content (e.g., transparent messages about side effects), modes, and access points (e.g., a variety of medical and non-medical sites), and trusted information sources (e.g., trusted leaders, Black doctors and researchers). Conclusions These insights can inform ways to improve initial and booster vaccination uptake as the COVID-19 pandemic progresses.